Adolescents' perception of parental love - Chua, Jacqueline V. (Animo Repository, 1998)
This paper compares adolescents' perception of parental love according to type of family (intact or broken), gender of the adolescent and gender of the parent. The study was done using a descriptive research design. Purposive sampling was used to select 63 adolescent subjects whose ages ranges from 16-20 years old. Thirty-three of the subjects came from intact families while the remaining 30 came from broken families. Self-administered, combination of open and close-ended questionnaires were used for data gathering. The results of the study exhibited that the male and female respondents did not differ in their perception of parental love, whether they came from an intact or broken family. The respondents primarily perceived parental love as showing care and concern, providing financial support, giving the freedom to make decisions, exerting discipline and giving respect. However, when the gender of the parent was considered, there was a more evident distinction. Both male and female respondents viewed the father as a financial supporter and disciplinarian while mothers manifested love in more emotional ways, like through caring and concern.